Offense of Spreading Infectious Disease and Methods of Proof Through Forensic Science - Ahmad Syukran Baharuddin; Wan Abdul Fattah Wan Ismail; Hasnizam Hashim; Muhammad Hazim Ahmad; Lukman Abdul Mutalib (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
International Seminar on Syariah and Law (INSLA 2020) E-Proceedings “Hala Tuju Syariah Dan Undang - Undang Mendepani Pandemik Covid - 19” Organized by : Faculty of Syariah and Law, Universiti Sains Islam Malaysia 27-28 October 2020